Effects of a Plastic-Free Lifestyle on Urinary Bisphenol A Levels in School-Aged Children of Southern Italy: A Pilot Study - Francesco Sessa (Frontiers in Public Health, 2021)
Bisphenol A (BPA) is an endocrine disruptor (ED) frequently used in food packaging. BPA is used as a monomer in the manufacture of some food packaging. This study aimed to evaluate the urinary BPA concentration in an Italian pediatric cohort, testing the levels of this ED over a period of 6 months, evaluating the effects of a diet regimen with a reduction of Plastic Food Packaging (PFP). One hundred thirty Italian children were enrolled and divided into two groups “School Canteen” and “No School Canteen.” The first group consumed one meal at school using a plastic-free service for 5 days/weeks, while the other group did not modify their normal meal-time habits. The BPA levels were tested in urine samples at three time points: T0, is the time before the application of the plastic-free regimen diet; T3, 3 months later; and T6, 6 months later. A reduction of urine BPA levels was detected in the “School Canteen” group. In particular, the reduction was significant analyzing both the intra (among the three testing times) group and inter (between “School Canteen” and “No School Canteen”) group variability. Our results show the effects of a diet regimen with a reduction of PFP, demonstrating a connection between urinary BPA levels and food packaging.